A Naturally Encoded Dipeptide Handle for Bioorthogonal Chan–Lam Coupling. Issue 15 (9th March 2018) - Ohata, Jun; Zeng, Yimeng; Segatori, Laura; Ball, Zachary T.
Abstract: Manipulation of biomacromolecules is ideally achieved through unique and bioorthogonal chemical reactions of genetically encoded, naturally occurring functional groups. The toolkit of methods for site‐specific conjugation is limited by selectivity concerns and a dearth of naturally occurring functional groups with orthogonal reactivity. We report that pyroglutamate amide N−H bonds exhibit bioorthogonal copper‐catalyzed Chan–Lam coupling at pyroglutamate‐histidine dipeptide sequences. The pyroglutamate residue is readily incorporated into proteins of interest by natural enzymatic pathways, allowing specific bioconjugation at a minimalist dipeptide tag. Abstract : Protein modification : The pyroglutamate‐histidine dipeptide sequence exhibits remarkably fast and efficient copper‐catalyzed N−H coupling with boronic acids, allowing specific and bioorthogonal functionalization at a natural posttranslational modification.